Dealing With Earthquake Disaster on Java 2006: A Comparison of Affected and Non-affected People - Evelin Witruk; Yumi Lee; Bagus Riyono; Amitya Kumara; Kathleen Otto (Faculty of Psychology, Universitas Surabaya, 2014)
The study investigated affected and non-affected people in Indonesia after the earthquake and the volcanic eruption in May 2006. We expected belief in a just world (BJW) and coping styles to be important factors when dealing with natural disasters for disaster attribution and psychopathological symptoms. Overall, 80 affected and 66 non-affected people were asked in the survey about their BJW, coping style, earthquake attribution, and psychopathological symptoms. ANOVAs and path models were used to analyze the data. Results show that people with a strong BJW attribute the disaster as a consequence of human failure. Avoidance coping was correlated with both emotional disturbance and psychological affectedness whereas approach coping was not related to the assessed psychopathological symptoms. Differences in the structural relations for the affected group emerged when compared to the non- affected group. Studi ini meneliti masyarakat di Indonesia yang terdampak dan yang tak-terdampak setelah gempa bumi dan letusan gunung berapi pada Mei 2006. Kami mengharapkan keyakinan terhadap dunia yang adil (DYA) dan gaya koping (coping styles) merupakan factor-faktor penting ketika berhadapan dengan bencana alam terkait atribusi kebencanaan dan gejala psikopatologis. Sejumlah 80 masyarakat terdampak dan 66 tak-terdampak diwawancarai dalam survei tentang DYA, gaya koping, atribusi gempa bumi, dan gejala psikopatologisnya. Untuk menganalisis data digunakan model ANOVA dan jalur. Hasil menunjukkan bahwa masyarakat dengan DYA kuat mengatribusikan bencana sebagai konsekuensi kegagalan manusia. Koping penghindaran berkorelasi dengan gangguan emosional dan akibat psikologis sedangkan koping pendekatan tidak berkorelasi dengan gejala psikopatologis yang dinilai. Perbedaan dalam hubungan struktural pada kelompok terdampak muncul bila dibandingkan terhadap kelompok yang tak-terdampak.